Development of a duplex-PCR for differential diagnosis of Xanthomonas phaseoli pv. manihotis and Xanthomonas cassavae in cassava (Manihot esculenta). (January 2019) - Flores, Carolina; Zarate, Carlos; Triplett, Lindsay; Maillot-Lebon, Véronique; Moufid, Yassine; Kanté, Moussa; Bragard, Claude; Verdier, Valérie; Gagnevin, Lionel; Szurek, Boris; Robène, Isabelle
Abstract: Cassava Bacterial Blight and Cassava Bacterial Necrosis are two bacterial diseases affecting cassava, respectively caused by Xanthomonas phaseoli pv. manihotis ( Xpm ) and Xanthomonas cassavae ( Xc ). Since both pathogens may be present on leaves and cause similar symptoms, we developed a new molecular diagnostic tool to detect and distinguish between Xpm and Xc . Based on genome sequences from the target species as well as from non-target species, in silico analysis was performed to select candidate primers through a novel strategy targeting specificity. Experimental validation enabled to establish a duplex-PCR diagnostic tool that will be useful for future surveillance programs and better disease control. Highlights: A duplex-PCR assay to detect and discriminate Xanthomonas phaseoli pv. manihotis and Xanthomonas cassavae . Selection of specific PCR primers sets from an original bioinformatics pipeline. Evaluation of primers specificity by experimental and in silico analyses. Molecular detection evidenced from field lesions, some collected in the 1970s.